(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
This study primarily focuses on feminism and the women’s movement and how they manifest in Macedonian society. The feminist ideology reflects various forms of activism, with the common goal of overcoming the subordinate status of women in society and achieving equality between men and women. Hence, this study explores the following questions: does feminist activism in Macedonian society contribute to the advancement of women’s rights, and can every women’s movement be situated within the framework of feminist theory? Consequently, through the analysis of specific activities, actions, and movements in public discourse, the relationships of the women’s movement with feminism will be explored, with an emphasis on their identification with the feminist movement. At the same time, this study will address questions of gender as a central analytical category in feminist discourse, as well as the discrepancy between equality as a universal value, on the one hand, and entrenched patterns of domination regarding gender and sexual orientation, on the other hand.